Intervensi Management Jalan Nafas Dalam Mengatasi Pola Nafas Tidak Efektif Di RSU Dr. Harjono Ponorogo - Abimanyu, Anindito; Purwaningsih, Yustina; Purwaningsih, Endang; Hendrawati, Gandes Widya; Hartanto, Agung Eko (Universitas Sultan Ageng Tirtayasa, 2024)
Tuberculosis is a disease caused by infection with the bacteria Mycobacterium tuberculosis which can attack the lungs and other organs. Manifestations of TB are characterized by shortness of breath, coughing, increased sputum production so that TB sufferers can experience problems with ineffective breathing patterns due to airway obstruction. This study aims to carry out and analyze nursing care for TB patients with ineffective breathing pattern problems. Case study research method. Data collection techniques use interviews, observation, physical examination and documentation studies. Data collection instruments used observation sheets, interview methods, and nursing care formats. Based on the results of the assessment, complaints of shortness of breath accompanied by coughing were found. The nursing diagnosis determined was ineffective breathing pattern. Nursing intervention with airway management is implemented for 3 x 24 hours. The results of the evaluation on the 3rd day of treatment showed that the breathing pattern had improved, as indicated by no complaints of shortness of breath, no nostril breathing, no use of accessory muscles for breathing, normal breathing pattern with improved respiratory frequency, SpO2 98% and regular breathing rhythm. The conclusion is that the problem of ineffective breathing pattern nursing can be improved with airway management interventions. Airway management interventions can be carried out to overcome problems with ineffective breathing patterns